2008
DOI: 10.1108/02632770810895705
|View full text |Cite
|
Sign up to set email alerts
|

Preferences of older people for environmental attributes of local parks

Abstract: Purpose -This study aims to examine the environmental attributes relevant to older people's preferences for neighbourhood open spaces. It also aims to explore the association between the relative importance of different environmental attributes and personal and social characteristics in a sample of older people covering a range of geographic locations in the UK. Design/methodology/approach -Choice-based conjoint analysis (CBC) was used to obtain responses from a sample of 237 older people (60 years þ ) living … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 22 publications
(17 reference statements)
5
56
0
Order By: Relevance
“…Similar to recent systematic review findings by Smith et al (2017), facilities and amenities like toilets and drinking fountains were reported by children in this study as important components of parks, fields, courts and reserves. This finding supports research with adults that shows these amenities are important for adults, particularly older adults (Alves et al 2008). Cohen et al (2015) found that recently renovated parks had higher visitation rates and overall greater levels of physical activity by children than unrenovated parks.…”
Section: Discussionsupporting
confidence: 79%
“…Similar to recent systematic review findings by Smith et al (2017), facilities and amenities like toilets and drinking fountains were reported by children in this study as important components of parks, fields, courts and reserves. This finding supports research with adults that shows these amenities are important for adults, particularly older adults (Alves et al 2008). Cohen et al (2015) found that recently renovated parks had higher visitation rates and overall greater levels of physical activity by children than unrenovated parks.…”
Section: Discussionsupporting
confidence: 79%
“…The purpose of this study is to address this. The results published here are a development of earlier published work (Alves et al, 2008) and illustrate innovative analytical approaches to understanding the relative importance of environmental attributes for groups and subgroups within the study sample of older people. They also show how modelling and scenario testing can be used to inform practical decisions about planning, design, and management of the environment to serve different user needs.…”
mentioning
confidence: 87%
“…For example, studies have highlighted that older participants of groupbased nature conservation and/or gardening activities appreciate the opportunities gained for: structure and routine (Gross and Lane, 2007); meaningful social interaction and the development of stronger community ties (Sullivan et al, 2004); a sense of achievement, pride and ownership (Townsend, 2006); and the forging of new social identities (Milligan et al, 2005). Older adults' decisions concerning participation in communal gardening activities, or the use of green spaces more generally, may be influenced by factors such as the presence of amenities, including toilets, seating areas and cafes (Alves et al, 2008;Aspinall et al, 2010). However, advancing age can limit older adults' capacity to cope with the garden, or to continue participating in social or community activities as they used to; these are changes in individual agency which may led to distress, frustration or even depression (Gross and Lane, 2007).…”
Section: The Influence Of Shifting Life Circumstances Over Timementioning
confidence: 98%